Antioxidant, Free Radical-Scavenging, and NF-κB-Inhibitory Activities of Phytosteryl Ferulates: Structure-Activity Studies - Md. Shafiqul Islam; Hiroshi Yoshida; Naoaki Matsuki; Kenichiro Ono; Reiko Nagasaka; Hideki Ushio; Ying Guo; Toshiyuki Hiramatsu; Takamitsu Hosoya; Takahisa Murata; Masatoshi Hori; Hiroshi Ozaki (Elsevier, 2009)
Some of the pharmacological properties of phytosteryl ferulates may be linked to their antioxidant potential. In this study, 2,2-diphenyl-1-picrylhydrazyl (DPPH), electron spin resonance (ESR), and thiobarbituric acid-reactive substances (TBARS) assays demonstrated that phytosteryl ferulates such as cycloartenyl ferulate (CAF), 24-methylenecycloartanyl ferulate (24-mCAF), and β-sitosteryl ferulate (β-SF) and ferulic acid (FA) each exerted strong free radical scavenging and antioxidation of lipid membrane, which were comparable to α-tocopherol. However, the sterol moiety alone, such as cycloartenol (CA), had neither activity. Since, the reactive oxygen species (ROS) production in the cell complex defense mechanism cannot be ruled out with the cell free system, we measured ROS production in NIH 3T3 fibroblast cells induced by H2O2. CAF and ethyl ferulate (eFA) greatly decreased the ROS level in this system. CA also significantly inhibited the ROS level, suggesting that CA could inhibit ROS production in living cells. Besides these, CAF, 24-mCAF, β-SF, as well as eFA and CA, all these chemicals significantly inhibited the NF-κB activity as analyzed by measuring translocation of NF-κB p65 in LPS-stimulated RAW 264.7 macrophages. These observations revealed that phytosteryl ferulates are responsible for the antioxidant and anti-inflammatory activity via ROS scavenging and inhibition of ROS production. Keywords:: phytosteryl ferulate, cycloartenyl ferulate, NF-κB, antioxidant, reactive oxygen species (ROS)